Beauvericin purification from fungal strain using molecularly imprinted cryogels. (February 2022) - Ulusoy, Meltem; Aslıyüce, Sevgi; Keskin, Nevin; Denizli, Adil
Graphical abstract: Highlights: Molecularly imprinted polymers show promise for one-step selective purification. Because of the large pores of cryogels, they can be used with cell lysates. Beauvericin has antibacterial activity. Beauvericin was purified from fungal source using a molecularly imprinted cryogel. The highest adsorption capacity of BEA-imprinted cryogel was 43 mg/g. Abstract: Beauveria bassiana is a wide host range entomopathogenic fungus that plays a substantial part to control of insect populations. During its pathogenic phase, fungus syntheses several metabolites. One of these metabolites is beauvericin (BEA) and it shows as an antibiotic, antifungal, insecticidal activity. Molecular imprinting approach allows selective and sensitive recognition of chosen template molecule by leaving artificial imprinted cavities in polymer matrix that provides high affinity and selectivity toward desired compound. Cryogels are gel matrices prepared by the method of cryotropic gelation performed below the freezing point of monomer solutions. Under these special conditions, the polymer material resulting from gel formation has rather unusual macroporous morphologies and processability. In this study, BEA-imprinted cryogel columns were prepared for purification of beauvericin from fungal extracts. According to the experimental results, optimum adsorption conditions were determined as pH 6.5 buffer solution, 1 mL/min flow rate and 25 °C. Under these conditions, the highest adsorption capacity of cryogels was found to be 43 mg/g. The adsorption isotherm is consistent with the Freundlich adsorption isotherm. In addition, BEA imprinted cryogels are 9.5 times more selective against the template molecule BEA than bassiatin, which is the competitive agent.